A qualitative study exploring patients' and carers' experiences of Early Supported Discharge services after stroke. (August 2013) - Cobley, Christine S; Fisher, Rebecca J; Chouliara, Niki; Kerr, Micky; Walker, Marion F
Objective: To investigate patients' and carers' experiences of Early Supported Discharge services and inform future Early Supported Discharge service development and provision. Design and subjects: Semi-structured interviews were completed with 27 stroke patients and 15 carers in the Nottinghamshire region who met evidence-based Early Supported Discharge service eligibility criteria. Participants were either receiving Early Supported Discharge or conventional services. Setting: Community stroke services in Nottinghamshire, UK. Results: A thematic analysis process was applied to identify similarities and differences across datasets. Themes specific to participants receiving Early Supported Discharge services were: the home-based form of rehabilitation; speed of response; intensity and duration of therapy; respite time for the carer; rehabilitation exercises and provision of technical equipment; disjointed transition between Early Supported Discharge and ongoing rehabilitation services. Participants receiving Early Supported Discharge or conventional community services experienced difficulties related to: limited support in dealing with carer strain; lack of education and training of carers; inadequate provision and delivery of stroke-related information; disjointed transition between Early Supported Discharge and ongoing rehabilitation services. Conclusions: Accelerated hospital discharge and home-based rehabilitation was perceived positively by service users. The study findings highlight the need for Early Supported Discharge teams to address information and support needs of patients and carers and to monitor their impact on carers in addition to patients, using robust outcome measures.